Bacterial DNA detection in blood using PCR/ESI-MS in neonates with suspected early onset infection - Sinha, Ajay K.; Saso, Anja; Mufunde, Arikana; Kempley, Steven T.; Wilks, Mark; Millar, Mike (Frontiers in Cellular and Infection Microbiology, 2025)
ObjectiveThe study aimed to assess the relationship between clinical features, routine laboratory parameters, including conventional blood culture, and identification of microorganisms by a commercial system of Polymerase Chain Reaction coupled with Electrospray Ionization Mass Spectrometry (PCR/ESI-MS) (Abbot Iridica) in infants with suspected early-onset infection.Study designProspective observational cohort study.SettingNeonatal intensive care unit and postnatal ward at a tertiary hospital within an urban setting.PatientsNeonates >=34 weeks gestation with clinically suspected early-onset infection between January 2016 and March 2017 were recruited. Blood samples were taken at the time of suspected infection for both blood culture inoculation (BacT/ALERT® system) and PCR/ESI-MS analysis (0.5ml). An electronic database was used to document demographic and clinical details.Results54 infants were studied with a median (IQR) gestational age and birth weight of 39.7 (37.5-41.0) weeks and 3.2 (2.7-3.5) kg respectively. 1 infant had both bacterial DNA detected on PCR/ESI-MS and bacterial growth on blood culture (Group B Streptococcus). 9 infants had bacterial DNA detected but with negative blood culture. The bacteria identified were Streptococcus sp (n=3) Sneathia (n=1), Cutibacterium acnes(n=6),. All infants with no bacterial DNA detected on PCR/ESI-MS also had a negative blood culture result. Infants with positive bacterial DNA identification in blood had significantly higher CRP values; initially (p=0.002), when repeated after 18-24 hours (p=0.02) and maximally within the first 72 hours (p=0.03). The proportion of infants with a CRP> 5 mg/L was significantly higher if bacterial DNA had been detected (p=0.01).ConclusionsPCR/ESI-MS detected bacterial DNA of organisms considered pathogenic in four times more blood samples than culture alone, and had a high sensitivity and negative predictive value. Bacterial DNA was detected by PCR/ESI-MS in infants who did not have bacterial growth on blood culture and this was associated with a raised inflammatory marker. It may be a useful tool to exclude sepsis in the neonatal cohort and reassess the need for prolonged antibiotic treatment. The results are promising but there is a need to improve blood collection methods to take advantage of the potential benefits of molecular detection.